How accurately can we measure vehicle fuel consumption in real world operation?. (January 2021) - Pavlovic, J.; Fontaras, G.; Broekaert, S.; Ciuffo, B.; Ktistakis, M.A.; Grigoratos, T.
Highlights: OBD accuracy is analysed for 15 LDVs and 12 HDVs. For most vehicles, OBD fuel consumed was measured with accuracy ± 5% (on-road and lab) For most vehicles, OBD distance was measured with accuracy ±1.5% (on-road and lab) The accuracy improves for monitoring over longer periods. High OBD accuracy is important for the quality of future monitoring real-world fuel consumption from road transport. Abstract: European Union (EU) regulations setting CO2 emission standards for light-duty (LDV) and heavy-duty vehicles (HDVs) require the Commission to monitor in-use fuel consumption (FC) using on-board fuel consumption monitoring (OBFCM) devices. For LDVs, the accuracy to measure fuel consumed is set by regulation to ±5%, while for HDVs no requirements exist so far. In this study, OBFCM data from 15 LDVs and 12 HDVs were recorded in lab and on-road trips. Results indicate that the fuel consumed measured by the OBFCM, for the majority of the vehicles, satisfies the accuracy requirements of ±5% over complete laboratory tests or complete on-road trips (maximum vehicle average uncertainty 7%). Statistical analysis showed that on-board diagnostics (OBD) accuracy can be impacted by the average vehicle speed, acceleration, and overall trip dynamicity. The lowest accuracy can be expected when vehicles are driven at low speeds under transient conditions. For most of the vehicles the distance calculated from the OBD speed signal has an accuracy within ±1.5% on-road when Global Positioning System (GPS) distance is used as a reference. Both HDV and LDV results, confirmed that OBD accuracy and precision in measuring fuel consumed and distance improved for monitoring over longer periods (complete trips vs short phases). The results of this study could be used to further support the standardization of OBFCM accuracy in vehicles, and the setup of the EU real-world CO2 emissions monitoring approach.